Updates on embryo production strategies - Baruselli, P. S.; Vieira, L. M.; Batista, E. O. S.; Ferreira, R. M.; Sales, J. N. S.; Gimenes, L. U. [UNESP]; Torres-Junior, J. R. S.; Martins, C. M.; Sa Filho, M. F.; Bo, G. A. (Brazilian Coll Animal Reproduction, 2015)
The embryo production technologies are used to enhance genetic progress through female and male lineages. Advances in the control of ovarian follicular wave emergence, superstimulation and ovulation with self-appointed treatments have facilitated donor and recipient management. However, these procedures can be influenced by several factors related to the animals and their management. Therefore, researchers continue to investigate the ideal reproductive environments and treatments to maintain the viability of the techniques and field applicability.
Keywords: ET; IVP; OPU; SOV; synchronization